New sample preparation techniques for the determination of Si isotopic compositions using MC-ICPMS - Georg, R; Reynolds, B; Frank, M; Halliday, A (2006)
Techniques for the purification of Si for the determination of its natural stable isotopic composition have in the past been based on the requirements for gas-source mass-spectrometry, rather than MC-ICPMS. For high precision analyses by MC-ICPMS it is essential to have very pure solutions and in this paper a new technique is presented for the separation and purification of Si from natural samples to improve the determination of isotope ratios. A method has been optimised based on alkaline fusion followed by ion-exchange chromatography. The application to natural samples, such as river water samples and silicate mineral/rock samples is demonstrated. Alkali fusion avoids the use of hydrofluoric acid (HF), which introduces difficulties for the determination of Si isotope ratios using MC-ICPMS. By eliminating HF a 30-40% increase in sensitivity is achieved as well as a marked enhancement of mass bias stability leading to a factor of 2 improvement in reproducibility. The cation-exchange method enables processing of very small samples (3.6 μg Si) and a rapid and effective separation of Si from other cationic species. The overall recovery of Si during the entire procedure is better than 98% and no Si isotope fractionation is generated. Matrix tests demonstrate that this method is suitable for silicates, and that typical sulphate and nitrate abundances of river waters have no effect on measured Si isotope composition. The latter aspect is vital for analysis of river waters since the technique does not separate dissolved Si (silicic acid) from ambient anionic species. Overall, the new method presents a faster, safer and more reliable way to measure Si isotopes via MC-ICPMS. © 2006 Elsevier B.V. All rights reserved.